2017
DOI: 10.1149/2.0881709jes
|View full text |Cite
|
Sign up to set email alerts
|

High Specific Energy Density Aqueous Lithium-Metal Chloride Rechargeable Batteries

Abstract: Here we show the feasibility of a novel high energy density battery with a Li anode and a MCl 2 (M = Fe, Co, Ni, Cu, and Zn) aqueous cathode separated by a water-stable NASICON-type lithium-ion conducting solid electrolyte of Li 1.4 Al 0.4 Ge 0.2 Ti 1.4 (PO 4 ) 3 (LAGTP). The Li/MCl 2 (M = Co, Ni, and Zn) aqueous solution with LiCl cells were successfully charged and discharged. In contrast, the Li/MCl 2 (M = Fe and Cu) cells were discharged, but they could not be charged, because FeCl 2 and CuCl 2 reacted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The calculated specific energy density of the cell generally depends on the specific area capacity [34], and the cell performance of a solid active material such as LiCoO2 in the lithium-ion batteries depends on the thickness of the electrode [35]. However, the cell performance of a cell with a liquid catholyte shows no significant dependence on the specific area capacity, as reported in the literature [11]. Hence, the proposed Li/BQS battery with a liquid catholyte could provide high energy density at a high area capacity.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The calculated specific energy density of the cell generally depends on the specific area capacity [34], and the cell performance of a solid active material such as LiCoO2 in the lithium-ion batteries depends on the thickness of the electrode [35]. However, the cell performance of a cell with a liquid catholyte shows no significant dependence on the specific area capacity, as reported in the literature [11]. Hence, the proposed Li/BQS battery with a liquid catholyte could provide high energy density at a high area capacity.…”
Section: Resultsmentioning
confidence: 72%
“…The specific energy density of the Li/LiMn2O4 cell based on the mass of the electrodes was estimated to be 446 Whkg -1 . Imanishi and co-workers [11][12][13] proposed a higher specific energy density aqueous lithium battery that consisted of a lithium anode with a liquid electrolyte, an aqueous MCl2 (M = Co, Ni, and Sn) solution catholyte, and a Li1.4Al0.4Ge0.2Ti1.4(PO4)3 (LAGTP) separator. The theoretical specific energy density of the Li/NiCl2 cell was as high as 1047 Whkg -1 based on the weights of lithium and NiCl2 and was at least twice of the conventional lithium-ion battery.…”
Section: Introductionmentioning
confidence: 99%
“…However, a major disadvantage of lead-acid batteries is their low energy density. In addition to aqueous lithium-air batteries, several other advanced aqueous rechargeable batteries have been proposed in the last few decades, including the aqueous lithium-metal chloride [32], aqueous lithium-Fe(CN) 6 3-/Fe(CN) 6 -4- [33], and aqueous Sn/LiCoPO 4 [34] batteries [10]. Among these, aqueous lithium-air battery, the one used in the present study as well, is reported with a high energy density of over 500 Wh kg -1 [27] and a low round-trip overpotential at a high current density of 2.0 mA cm -2 , in air and at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…3− /Fe(CN) 6 4− redox couple, and Imanishi and colleagues (Morita et al, 2017(Morita et al, , 2018Watanabe et al, 2019) proposed an aqueous lithium battery with a lithium anode and an aqueous MCl 2 /M (M = Sn, Co, and Ni) redox couple. Wu and colleagues reported a lithium battery using an aqueous electrolyte solution with a lithium anode and a LiFePO 4 (Hou et al, 2013;Chang et al, 2016), LiCoO 2 (Wang et al, 2013b), or LiMn 2 O 4 (Wang et al, 2013a) cathode.…”
Section: Introductionmentioning
confidence: 99%